Bamboo resource in Ibadan and environs; utilizations, opportunities and challenges (2009)
This paper reports the mode of harvest, treatment, current uses, cost and constraints to production of furniture and allied product from bamboo as well as the marketing potentials of such products in lbadan, Oyo state, Nigeria and Environs, About 264 respondents comprising farmers, allied furniture makers, marketers and consumers, construction workers, researchers and forestry employees were selected from the eleven LGAs in Ibadan, Oyo State, Nigeria and Environs. Data collected was subjected to descriptive statistical analysis. Bamboo was found in homestead farms and forests. It is free for public use and traditional harvesting techniques still applied in the study area. Bambusa vulgaris, Schrad was found to by respondents to be the most prominent specie. They were also observed by respondents to be relevant in round and un-treated form for making local beds (18.2%), construction purpose (48.2%), as firewood (28.4%), stacking stand and others (5.2%). Large market opportunities exist for bamboo furniture and related products provided the impediment to its use. viz: lack of technological knowhow, equipment and enlightenment can be removed .This study established that bamboo resources in Ibadan and environ if properly harness can expand job opportunities and provide livelihood to large segments of rural/semi-urban populations in the study area.